The Effects of Quality Management Practices on Key Results: questionnaires sample for the industry of tourist accommodation in Spain - Álvarez García, José; del Río Rama, María de la Cruz; Vila Alonso, Mercedes (Review of Business Management, 2014)
In this research work, we examine the direct and indirect effects of quality management practices on key results and we identify the relationship between quality practices. To achieve the proposed objective, a structural model was used, taking into account the previous review of the literature, in order to identify the quality practices and causal relationships with the key results. The theoretical model and hypotheses are tested using data collected from a sample of 186 tourist accommodation companies certified with the “Q for Tourist Quality” standard in Spain, from a questionnaire based on quality practices identified in the literature and on the EFQM Model, taking some of the most relevant scales as a reference. The methodology used consists of the application of an Exploratory and Confirmatory Factorial Analysis to validate the scales (reliability, one-dimensionality and validity) and define the number of items of each of the measuring instruments of the constructs proposed, to then estimate the causal model proposed, proceeding to test the hypotheses formulated by using the Structural Equation Model (SEM) technique. The results achieved support the relationship between quality practices and the direct and positive impact of two of the practices, processes management and quality policy/planning, on the key results. It was also observed that the quality practices that most influence key results are quality policy/planning along with leadership, when considering the total effects (direct and indirect).